Developing Turn-Based Multiplayer Games with GameMaker Studio 2 and NodeJS - Rajiv, Yadu (Apress, 2018)
Create your first turn-based multiplayer game using GameMaker Studio 2's built-in networking functions as well as using a simple NodeJS server. This book introduces you to the complexities of network programming and communication, where the focus will be on building the game from the ground up. You will start with a brief introduction to GameMaker Studio 2 and GML coding before diving into the essential principles of game design. Following this, you will go through an introductory section on NodeJS where you will learn how to create a server and send and receive data from it as well as integrating it with GameMaker Studio. You will then apply multiplayer gaming logic to your server and unlock multiplayer game features such as locating a player, syncing their data, and recording their session. You will: • Discover the architecture of GameMaker Studio 2 • Master GameMaker Studio 2's built-in networking functions • Integrate GameMaker Studio 2 with NodeJS • Add new features to your game with NodeJS modules.